First port of call: facing the parents of autism spectrum disorder - Debbie L. Fewster; Thavanesi Gurayah (South African Family Practice)
Background: Autism spectrum disorder (ASD) is a debilitating condition for the child as well as the parents and family. Research in ASD is on the increase with many studies coming out of developed countries. To add to the knowledge base in ASD from a South African perspective, the experiences and coping strategies of parents of children with ASD were explored.